1991
DOI: 10.1038/nbt0691-553
|View full text |Cite
|
Sign up to set email alerts
|

DNA Amplification Fingerprinting Using Very Short Arbitrary Oligonucleotide Primers

Abstract: The surprising finding that amplification of genomic DNA can be directed by only one oligonucleotide primer of arbitrary sequence to produce a characteristic spectrum of short DNA products of varying complexity, was applied as a strategy to detect genetic differences between organisms. This approach, DNA amplification fingerprinting (DAF), does not depend on cloning or DNA sequence information and can generate fingerprints from DNA of viral, bacterial, fungal, plant and animal origins. Primers as short as 5 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
175
0
8

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(187 citation statements)
references
References 32 publications
4
175
0
8
Order By: Relevance
“…AFLPs. Amplification fragment length polymorphisms (AFLPs) are DNA fragments with different nucleotide sequences (Caetano-Anolles et al 1991), of which millions of copies have been synthesized (i.e., amplified) via the polymerase chain reaction [(PCR), Mullis et al 1986;Erlich et al 1991]. Only the DNA sequence interval (several thousand nucleotides) between the sites where one or more base pairs (bp) of polynucleotide (15 to 35 bp) or oligonucleotide (2 to 10 bp) primers anneal to a DNA template is so amplified.…”
Section: Dnamentioning
confidence: 99%
“…AFLPs. Amplification fragment length polymorphisms (AFLPs) are DNA fragments with different nucleotide sequences (Caetano-Anolles et al 1991), of which millions of copies have been synthesized (i.e., amplified) via the polymerase chain reaction [(PCR), Mullis et al 1986;Erlich et al 1991]. Only the DNA sequence interval (several thousand nucleotides) between the sites where one or more base pairs (bp) of polynucleotide (15 to 35 bp) or oligonucleotide (2 to 10 bp) primers anneal to a DNA template is so amplified.…”
Section: Dnamentioning
confidence: 99%
“…Gresshoff and colleagues have shown that primers as short as five bases could be used for PCR (2). However, short primers of 5 or 6 bases, while they would occur frequently in the list of interest, would also occur frequently in other RNAs and therefore might not generate any significant selectivity for the mRNAs in our list of interest.…”
Section: Program Design and Resultsmentioning
confidence: 99%
“…Native B. thuringiensis isolates, retrieved from different locations (Table 1), were subjected to randomly amplifi ed polymorphic DNA (RAPD) marker-based analysis for characterization of their genetic diversity. Recently, various techniques that rely on different nucleic acid pattern and discriminate at genetic level have been developed to gain information about the genetic diversity and genetic relationship between different organisms [5][6][7]. The RAPD markerbased analysis was found to be an easy, quick and reliable technique to assess the diversity of different types of organisms [8,9] and this technology was successfully applied to characterize the genetic diversity in various B. thuringiensis isolates [10].…”
Section: Introductionmentioning
confidence: 99%